On the intrinsic value of democracy - N. A. Shaveko (Управление)
The article aims to consider the most common arguments in support of democracy as a procedure for making general decisions that is fair in itself, and not in terms of the result achieved. The methods of critical, logical, and normative analysis typical for this kind of research are used. Since the intrinsic value of the democratic procedure is usually justified with reference to three basic principles, people’s self-government, political equality and majority rule, the three tasks of the article are to consider each of them. It is shown that the ideal of self-government is not absolute even at the individual level; if we talk about the self-government of an entire people, then we have to state that the concepts of the will of the people, collective will or common will are fiction that has no real meaning without reference to a specific voting procedure. It is demonstrated that the political equality is also not an absolute value, and often seemingly habitual and justified political institutions directly proceed from a violation of the principle of the political equality. As a result, it is concluded that the intrinsic value of the democracy is evident only when we accept two ideals at once – individual self-government and political equality – and at the same time deny the existence and knowability of the substantive ideal of justice. Finally, the principle of decision-making by an absolute majority of votes is investigated as the principle underlying many normative justifications of the democracy. An analysis of the arguments given in support of the majority rule reveals not only the dependence of these arguments on specific circumstances, but also that almost all of them refer to substantive rather than procedural criteria. In other words, the majority principle – as well as other collective decision-making procedures – is valued more by the results it leads to than by itself.